تأثير الرش بحمض الصفصاف Salicylic acid في بعض مؤشرات النمو والإنتاج لنبات الفاصولياء Phaseolus vulgaris L. صنف Tema - صهيوني فهد; حمامي حنان; شريقي رغداء (Latakia University Journal -Biological Sciences Series, 2019)
The experiment was carried out at the end of April during 2018. In Ain-Abaida In Lattakia in order To study effect of Salicylic acid Foliar spry on the growth and yield snap bean (Phaseolus vulgaris L.) Tema Varity (limited growth) with four concentration (0, 25, 50, 100) ppm, after 25-35 days farming in early morning till full wet, and the experiment was laid according to randomized block design. Results showed that spray treatment with salicylic acid at concentration of (50 ppm) was significant in the studied parameter such as: Leaf area (5224.667 cm2), Leaf area index (3.63), number of clusters (18.5 cluter/plant), number of pods (35.66 pod/plant), plant yield (331.71 g/plant). Compared to control plants that were respectively: (2180.26 cm2), (1.18) (7.4 cluster/plant), (18.5 pod/plant), (94.7 g/plant). هدف هذا البحث إلى دراسة تأثير الرش بحمض الصفصاف Salicylic acid بأربعة تراكيز (0، 25، 50، 100) ppm في نمو وإنتاجية نبات الفاصولياء الخضراء Phaseolus vulgaris L. صنف Tema (محدود النمو) بعد 25و35 يوم من الزراعة في الصباح الباكر وحتى البلل التام, صُممت التجربة وفق تصميم القطاعات العشوائية ونُفذت في أواخر شهر نيسان عام 2018 في مزرعة خاصة في منطقة عين البيضا التابعة لمحافظة اللاذقية . أظهرت النتائج تفوق معاملة الرش بتركيز 50ppm معنوياً في مؤشرات النمو و الإنتاج المدروسة حيث بلغ متوسط المساحة الورقية (5224.667سم2), ودليل المسطح الورقي (3.63), وعدد النورات الزهرية (18.5نورة/نبات), عدد القرون (35.66 قرن / نبات), إنتاج النبات (331.71 غ /نبات), بالمقارنة مع النباتات الشاهد التي بلغت على التوالي: (2180.26 سم2), (1.18), (7.4), (18.5 قرن /نبات), (94.7 غ /نبات).